2021
DOI: 10.13181/mji.oa.204395
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of infraorbital block using ketamine 1% for intra- and postoperative analgesia in children for ambulatory cleft lip correction

Abstract: BACKGROUND In Indonesia, cleft lip correction surgery is often done as a social program in remote areas with limited resources. This study aimed to assess the effectiveness of ketamine, a cheaper and more accessible alternative, as a local analgesia in infraorbital block and to determine the possibility of ketamine as an alternative local analgesic drug for intraoperative and postoperative periods. METHODS This was a randomized controlled trial in children aged 2 months to 5 years who underwent cleft lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Compared with IV pentazocine, Grewal et al32 found that infraorbital nerve block with 0.25% bupivacaine resulted in greater duration of analgesia (357.5versus 231 min; P <0.001), as well as fewer patients requiring supplementary analgesics (16.6% versus 76.6%). When compared with bilateral infraorbital nerve block with 1% ketamine (0.5 mL), Ramlan et al33 found that 0.25% bupivacaine (0.5 mL) resulted in similar pain scores, whereas ketamine provided a longer duration of analgesia ( P =0.031). Another study found morphine consumption to be lower ( P =0.033) in cleft palate patients receiving bilateral suprazygomatic maxillary nerve block with 0.15 mL/kg ropivacaine (0.2%) compared with saline 18.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Compared with IV pentazocine, Grewal et al32 found that infraorbital nerve block with 0.25% bupivacaine resulted in greater duration of analgesia (357.5versus 231 min; P <0.001), as well as fewer patients requiring supplementary analgesics (16.6% versus 76.6%). When compared with bilateral infraorbital nerve block with 1% ketamine (0.5 mL), Ramlan et al33 found that 0.25% bupivacaine (0.5 mL) resulted in similar pain scores, whereas ketamine provided a longer duration of analgesia ( P =0.031). Another study found morphine consumption to be lower ( P =0.033) in cleft palate patients receiving bilateral suprazygomatic maxillary nerve block with 0.15 mL/kg ropivacaine (0.2%) compared with saline 18.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the included studies investigated the use of various analgesia techniques that aimed at reducing postoperative opioid consumption 2,14–29. Seven of the included studies investigated the effectiveness of bupivacaine for use in nerve block in cleft lip and/or palate repair 1,4,28,30–33. All but 11 focused on infraorbital nerve block placement in cleft lip surgery patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations